Коллекция находок из раскопок М.К. Каргера 1948 г. на усадьбе Киевского исторического музея - Хамайко, Н.В. (Археологія і давня історія України, 2014)
В статье публикуются материалы коллекции
№ 100 Научных фондов ИА НАНУ, происходящей из
раскопок 1948 г. на усадьбе Киевского исторического музея (к юго-западу от фундаментов Десятинной церкви); анализируется состав коллекции относительно инвентарной описи 1948 г. из Научного
архива ИА НАНУ и данных о материалах раскопок М.К. Каргера в Санкт-Петербурге (Россия). Розкопки М.К. Каргера на території Київського
історичного музею 1948—1949 рр. зосереджувалися
поблизу решток Десятинної церкви, на південний
захід від її фундаментів. Завдяки двом розкопам і шурфу у 1948 р. вдалося виявити значну колекцію
матеріалів, частина з яких зберігається у Наукових фондах ІА НАНУ як колекція № 100. M.K. Karger’s excavations in 1948 and 1949 at the
area of Kyiv Historical Museum were concentrated near
the Desiatynna church’s remains, at the south-west
from its foundation. In 1948, two excavated sections
and exploration trench revealed a significant collection
of materials, some of which are stored in the scientific
funds of the IA NASU as a collection 100. It contains
both the artefacts of everyday life (the bottom piece of
a glazed bowl with decoration «sgraffito», fragments
of glassware, jewellery, amber, and of a copper alloy
object, pyrophyllite spindles, and a piece of dressed
leather), and the building remains (fragments of panes, frescoes, glass and stone mosaics). Among the artefacts there are prepared bone and semi-melt glass mass which evidence for the craft production. Archaeological objects are separated into two chronological groups: finds from the pre-Mongol Rus layers and Modern Age finds. One object (bottom of faceted glass bottle) comes from 1948 M.K. Karger’s excavations at the territory of the St. Michael’s Golden-Domed Monastery.